Moral damage in re ipsa: Using the 'maxims of experience' as a probative placebo. - Daza Lozada, Carlos Adrián (Revista de Derecho, 2025)
Moral damage has long been regarded as a type of harm that is difficult to prove, due to its mental, subjective, and transient nature. To avoid the demand for direct evidence, legal doctrine and case law have promoted its treatment as damage in reipsa, inferring its existence through the use of maxims of experience. In these inferential operations, maxims of experience function as tools to connect the occurrence of certain known facts with the unknown and unproven existence of emotional suffering constituting the moral damage. However, this paper argues that such maxims often fail to meet the epistemic requirements that would justify their application, instead operating as probative placebos: they “legitimize” decisions by simulating correctness, without satisfying the minimum conditions for rational use.
Keywords: moral damage; tort law; evidence; maxims of experience; evidentiary; reasoning